Climate Risk Analysis Related to Urban Heat Islands in Metropolitan Areas for Urban Health: The Case Study of The Florence Plain - Del Duca, Bianca; Gullì, Enrico; Pisano, Carlo; Cristiano, Silvio (Contesti. Città, territori, progetti, 2026)
Urban heat islands (UHI) have become a widespread phenomenon in metropolitan areas worldwide, manifesting as an increase in the average ground surface temperature in urban environments compared to suburban areas. Climate change and intensified urbanization exacerbate this process, making it a key challenge of our time. In this context, urban planning plays a crucial role in developing UHI mitigation plans and adaptation strategies aimed at enhance urban livability and climate resilience. This research carries out a model for assessing and tackling climate risk associated with UHI in the Piana Fiorentina area, focusing on areas where thermal stress and population sensitivity are especially high, making heat-reduction interventions a priority. The study also proposes targeted responses and simulates the effectiveness of various design solutions for mitigating UHI effects and implementing adaptation strategies, highlighting the potential to adapt this method to other metropolitan areas.